Porous Materials Based on Bombyx Mori Silk Fibroin (Journal of Fiber Bioengineering and Informatics, 2018)
Bombyx mori silk fibroin (SF) is one of the most important fibers among biomedical porous materials due to its superior machinability, and biocompatibility. It is also chosen for its biodegradability and bioresorbability. It is a protein-based fiber. In this paper, we have reviewed the key features of SF. Moreover we have focused on the morphous, technical processing and biocompatibility of SF porous materials. We have also dealt with its application in research. Finally, a perspective on potential applications and problems of SF porous materials were provided.
Keywords: Bombyx mori silk fibroin; porous materials; processing; biomaterial; application; biocompatibility; biodegradation